Proposta de sistemática operacional para implantação de sistemas de gestão ambiental em empreendimentos industriais - Dalfre, Gabriel [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The implantation of environmental management systens (SGA) in companies is the first step to the company conquers the environmental certification and consequently the benefits of a sustainable production of products, services and activities can bring. However, in the way as they are proposals in bibliographies the implantation of the SGAs, does not identify the definition of the operational stages of implementation of the same ones, generating doubts on the real environmental and administrative performance that they can come to generate for the organization. In this direction, the present research brings a proposal of operational systematics for implantation of SGA in companies, detailing each stage of implantation, considering its particularitities. For in such a way, a revision of norm NBR ISO 14001:2004 was made, looking for to identify to the interpretation imperfections gifts in the normative system. Moreover, other methods of SGA implantation had been searched gifts in the bibliography, searching proposals that detailed the operational aspects of the implantation of the system. In the same way, the accomplishment of a period of training supervised in the first semester of 2007 made possible the practical experience of the functioning of a system of environmental management, beyond the contact with professionals of the area and the acquisition of documents that had helped in the development of the research. The result was the attainment of a detailed procedure more, defining the operational systematic of SGA implantation, beyond the generation of a flowchart, describing as to develop each stage. This detailing certainly will facilitate the implantation of a SGA in companies interested in improving its environmental performance.

A implantação de sistemas de gestão ambiental (SGAs) em empreendimentos é o primeiro passo para que uma empresa conquiste a sua certificação ambiental e, conseqüentemente, os benefícios que uma produção sustentável de produtos, serviços e atividades possa trazer. Porém, da maneira como são propostas nas bibliografias a implantação dos SGAs, não se identifica a definição das etapas operacionais de implementação dos mesmos, gerando dúvidas sobre o real desempenho ambiental e administrativo que eles possam vir a gerar para a organização. Nesse sentido, a presente pesquisa traz uma proposta de sistemática operacional para implantação de SGA em empreendimentos, detalhando cada etapa de implantação, considerando suas particularidades. Para tanto, foi realizada uma revisão da norma NBR ISO 14001:2004, procurando identificar as falhas de interpretação presentes no sistema normativo. Além disso, foram pesquisados outros métodos de implantação de SGA presentes na bibliografia, buscando propostas que detalhassem os aspectos operacionais da implantação do sistema. Da mesma forma, a realização de um estágio supervisionado no primeiro semestre de 2007 possibilitou a vivência prática do funcionamento de um sistema de gestão ambiental, além do contato com profissionais da área e a aquisição de documentos que ajudaram no desenvolvimento da pesquisa. O resultado foi a obtenção de um procedimento mais detalhado, definindo as etapas operacionais de implantação de SGA, além da geração de um fluxograma, descrevendo como desenvolver cada etapa. Esse detalhamento certamente facilitará a implantação de um SGA em empresas interessadas em melhorar seu desempenho ambiental.
Keywords: Engenharia ambiental; Qualidade ambiental; Engenharia Ambiental; Qualidade Ambiental; Environmental Engineering